1996
DOI: 10.1046/j.1365-2133.1996.131866.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of bullous pemphigoid with pulsed intravenous cyclophosphamide

Abstract: Pulsed therapy with intravenous cyclophosphamide was successful in a patient with bullous pemphigoid whose disease had proved resistant to other treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Three cases have been reported in which cyclophosphamide appeared to have a beneficial effect in otherwise refractory BP 82–84 …”
Section: 0 Managementmentioning
confidence: 99%
“…Three cases have been reported in which cyclophosphamide appeared to have a beneficial effect in otherwise refractory BP 82–84 …”
Section: 0 Managementmentioning
confidence: 99%
“…Although cyclophosphamide is often used to treat ocular cicatricial pemphigoid, several case reports have suggested that cyclophosphamide may also be useful in cases of severe or refractory BP when given in either oral daily (1–5 mg/kg/d) or pulse intravenous dosing. 40,41 No large or randomized trials have been performed using this medication.…”
Section: Bullous Pemphigoidmentioning
confidence: 99%
“…Our case is unique in terms of the unresponsiveness of BP to conventional therapeutic regimens 1–5 . Even combination of cyclophosamide pulse 6 and immunoadsorption, 7 which are reported to be effective for therapy refractory cases failed to suppress blister formation. Only CysA, a non‐standard therapy in the management of BP, showed some positive short‐term effect.…”
mentioning
confidence: 80%
“…Bullous pemphigoid (BP) is an acquired autoimmune subepidermal blistering disease of the skin that predominantly affects the elderly and usually responds effectively to conventional therapeutic regimens 1–7 . We describe a 53‐year‐old woman who presented uncommon clinical and biological features of BP such as young age, mucosal involvement and lack of efficacy to any standard therapies.…”
mentioning
confidence: 99%